Adoptive NK Cell Therapy - a Beacon of Hope in Multiple Myeloma Treatment - Vu, Son Hai; Pham, Ha Hong; Pham, Thao Thi Phuong; Le, Thanh Thien; Vo, Manh-Cuong; Jung, Sung-Hoon; Lee, Je-Jung; Nguyen, Xuan-Hung (Frontiers in Oncology, 2023)
Major advances in the treatment of multiple myeloma (MM) have been achieved by effective new agents such as proteasome inhibitors, immunomodulatory drugs, or monoclonal antibodies. Despite significant progress, MM remains still incurable and, recently, cellular immunotherapy has emerged as a promising treatment for relapsed/refractory MM. The emergence of chimeric antigen receptor (CAR) technology has transformed immunotherapy by enhancing the antitumor functions of T cells and natural killer (NK) cells, leading to effective control of hematologic malignancies. Recent advancements in gene delivery to NK cells have paved the way for the clinical application of CAR-NK cell therapy. CAR-NK cell therapy strategies have demonstrated safety, tolerability, and substantial efficacy in treating B cell malignancies in various clinical settings. However, their effectiveness in eliminating MM remains to be established. This review explores multiple approaches to enhance NK cell cytotoxicity, persistence, expansion, and manufacturing processes, and highlights the challenges and opportunities associated with CAR-NK cell therapy against MM. By shedding light on these aspects, this review aims to provide valuable insights into the potential of CAR-NK cell therapy as a promising approach for improving the treatment outcomes of MM patients.